RECONCILIATION, MEMORY AND FORGETTING: POLITICAL AND ETHICAL DILEMMAS. THE CASE OF CHILE - Lira, Elizabeth (Psyke & Logos, 2009)
This paper reflects on some questions on political and psychosocial dilemmas of political reconciliation in Chile. In the political transition period in Chile and in most of the Latin American countries there has been much discussion about truth, justice, social reparation, reconciliation, impunity, memory, overcoming memory, and suppressing memory. These are simultaneously political and sociopsychological problems, for individuals and for societies. It has been necessary to integrate in a more explicit way the connections between psychology and politics, between private stories, testimonies, and sociopolitical history.